2009
DOI: 10.3171/2009.4.peds08322
|View full text |Cite
|
Sign up to set email alerts
|

Role of Rac1-regulated signaling in medulloblastoma invasion

Abstract: Object Medulloblastomas are the most common malignant brain tumors in children. These tumors are highly invasive, and patients harboring these lesions are frequently diagnosed with distant spread. In this study, the authors investigated the role of Rac1, a member of the Rho family of small guanosine triphosphatases, in medulloblastoma invasion. Methods Three established medulloblastoma cell lines were us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 43 publications
1
16
0
Order By: Relevance
“…Rac1 activation is correlated with the progression of many types of cancer such as pancreatic cancer, gastric cancer, and breast cancer [29][33]. More investigations have revealed that Rac-dependent cell signaling activation can promote cell adhesion, migration, invasion and metastasis in a variety of cancers, such as prostate cancer, breast cancer, hepatocellular carcinoma, colon carcinoma and renal carcinoma, suggesting that Rac1 plays an important role in tumorigenesis and carcinoma progression [31], [34], [35]. In this study, we confirmed that Rac1 is overexpressed in osteosarcoma.…”
Section: Discussionmentioning
confidence: 99%
“…Rac1 activation is correlated with the progression of many types of cancer such as pancreatic cancer, gastric cancer, and breast cancer [29][33]. More investigations have revealed that Rac-dependent cell signaling activation can promote cell adhesion, migration, invasion and metastasis in a variety of cancers, such as prostate cancer, breast cancer, hepatocellular carcinoma, colon carcinoma and renal carcinoma, suggesting that Rac1 plays an important role in tumorigenesis and carcinoma progression [31], [34], [35]. In this study, we confirmed that Rac1 is overexpressed in osteosarcoma.…”
Section: Discussionmentioning
confidence: 99%
“…The overexpression of RAC1, a member of the RHO protein super-family, has been previously shown in DAOY cells and in medulloblastoma tumors and RAC1 activity is known to functionally regulate DAOY cell migration [21,22]. Our result shows significant activation of RAC1 when DAOY cells are stimulated with BMEN1 CM and to a lesser degree with DAOY CM (Fig.…”
Section: Resultssupporting
confidence: 73%
“…However, we found that 24 h ARQ197 pretreatment was necessary to block acute, HGF-induced c-Met signaling (Figure 2 C). c-Met can activate the c-Jun N-terminal kinase (JNK) (Rodrigues et al 1997 ), which controls growth and invasion of MB cells (Zavarella et al 2009 ). Consistently, we detected PHA-665752-sensitive phosphorylation of mainly the p46 isoform of JNK within five to ten minutes of HGF stimulation (Figure 2 D).…”
Section: Resultsmentioning
confidence: 99%